Development Of Injectable Carbonate Apatite Bone Bstitute Based on Phasetransformation Of Gypsum and Calcium Hydroxide: Preliminary Studies on Factors Influencing Carbonate Apatite Synthesis - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
Bone tissue is one of the most frequently used tissues for transplantation. The use of autologous bone grafts is still considered to be the golden standard, but there are several major disadvantages in this technique, for example: (1) low availability of transplantable tissue. (2) postoperative morbidity. (3) lack of functional shape of the transplant. Therefore, the development of alternatives to autologous bone is a very relevant issue in biomedical sciences to support bone reconstructive surgery. Among the alternative materials, carbonate apatite (C-Ap) has been a most likely candidate for bone substitutes with a superior biodegradation. In view of this. our collaborative research has resulted in the development of hydroxyapatite or carbonate apatite monolith by treatment of gypsum and calcium hydroxide in C02 and phosphate solution. Injectable C-Ap is then becoming our next goal. The cement can be applied directly into a bone defect. and can be shaped and molded to fit the required shape of the bone defect. In addition, the bone regenerative capacity of this C-Ap cement can further be enhanced by the inclusion of degradable polymeric microparticles with bone growth stimulating factors. The aim of this study is to understand the effect of carbonate source. magnesium suppression, and aging time on the crystallinity of carbonate apatite synthesis. The result shows that both aging time and Mg suppression do not influence crystallinity shown from the XRD pattern and FTIR spectra. The carbonate source does not influence the XRD patterns as well. It is suggested in the next continuing studies have been running in our laboratories to find friendly and simple method of apatite synthesis to prepare biodegradable apatite composite for biomedical purposes.